QTL for seed shattering and threshability in intermediate wheatgrass align closely with well‐studied orthologs from wheat, barley, and rice. Issue 3 (9th October 2021) - Altendorf, Kayla R.; DeHaan, Lee R.; Larson, Steve R.; Anderson, James A.
Abstract: Perennial grain crops have the potential to improve agricultural sustainability but few existing species produce sufficient grain yield to be economically viable. The outcrossing, allohexaploid, and perennial forage species intermediate wheatgrass (IWG) [ Thinopyrum intermedium (Host) Barkworth & D. R. Dewey] has shown promise in undergoing direct domestication as a perennial grain crop using phenotypic and genomic selection. However, decades of selection will be required to achieve yields on par with annual small‐grain crops. Marker‐aided selection could accelerate progress if important genomic regions associated with domestication were identified. Here we use the IWG nested association mapping (NAM) population, with 1, 168 F1 progeny across 10 families to dissect the genetic control of brittle rachis, floret shattering, and threshability. We used a genome‐wide association study (GWAS) with 8, 003 single nucleotide polymorphism (SNP) markers and linkage mapping—both within‐family and combined across families—with a robust phenotypic dataset collected from four unique year‐by‐location combinations. A total of 29 quantitative trait loci (QTL) using GWAS and 20 using the combined linkage analysis were detected, and most large‐effect QTL were in common across the two analysis methods. We reveal that the genetic control of these traits in IWG is complex, with significant QTL across multiple chromosomes, sometimes within and across homoeologous groups and effects that vary depending on the family. In some cases, these QTL align within 216 bp to 31 Mbp of BLAST hits for known domestication genes in related species and may serve as precise targets of selection and directions for further study to advance the domestication of IWG. Core Ideas: The two forms of shattering in intermediate wheatgrass are under independent genetic control. A QTL for brittle rachis type shattering was within 216 bp of an ortholog of Btr2 . A floret shattering QTL on chromosome 11 is likely novel to intermediate wheatgrass. Similar to wheat, threshability QTL were found primarily on Group 2 chromosomes. Previous research on annual cereals has informed the domestication of intermediate wheatgrass.